Takotsubo cardiomyopathy. Literature review: clinical performance, diagnostic algorithm, treatment, prognosis. Part II - S. A. Boldueva; D. S. Evdokimov (Российский кардиологический журнал, 2022)
Up-to-date data on the problem of takotsubo cardiomyopathy, including data on the clinical manifestations, diagnostic algorithm and treatment approaches, as well as the prognosis of possible complications is presented in review.